Social Media Usage and Gender - Nathasya Mohd Kamal; Nurul Zaitul Itri Alias; Wan Nor Hidayah Wan Afandi (Human Sustainability Procedia, 2022)
This study aimed to investigate how social media usage between gender. The findings of this study will contribute to precautions that can be made for the general public to navigate better social media usage. This study applied the theory of media richness theory. The quantitative method used in the research is the quantitative method and the data were collected from 120 volunteer students from universities across Malaysia. The findings showed there is no relationship between social media usage and gender. Thus, this study contributes to the communication field related to communication in a new era.